School Choice: An analysis of parental and primary school perspectives on attracting students to All Saints’ School, Mansfield. - Yates, Emily (2013)
Drawing on key social and educational research, this study considers the factors taken in to account when parents decide on a secondary school on behalf of their children. It centers on research conducted during the final term of the academic year 2012-2013 for All Saints’ School in Mansfield, England with the objective of delivering a marketing plan; it strives to identify and outline factors important to parents. Further, the influence of primary school head teachers in the secondary school choice decision is introduced. Research interviews were held with a number of parents and head teachers of local primary schools; key findings are outlined. Existing quantitative data provided by the school was used to validate the impact of location and journey distance on applications over a three year period and to draw conclusions in combination with the qualitative data. The outcomes are reviewed and considered in terms of business and marketing implications for the school. In particular, the concept of market orientation is considered in the context of public sector organisations in general and schools in particular, and the concept of market segmentation is discussed, based on existing theory, with several recommendations for the application of this concept in the context of the study.